Multi-method, longitudinal study on behavioral, emotional, and developmental factors of children in residential care in Lower Austria: A study protocol - Sarah Buttler-Stöbich; Rachel Dale; Katja Haider; Doris Mayerhofer; Raphaela Kohout; Ilona Horwath; Christoph Pieh (PLoS ONE, 2026)
Background In Austria, there is a significant research gap concerning the quality of out-of-home care (OoHC) provisions and their capacity to promote children’s well-being and development. Given the intrusive nature of such interventions, thorough evaluation is essential. This study protocol outlines a multi-method, long-term, and multi-perspective study that investigates: 1) the circumstances leading to full-time residential care placements; 2) the development of behavioral, emotional, and social factors over time; 3) key factors influencing children’s outcomes in residential care 4) the structure and everyday reality of residential care in Lower Austria, a federal state of Austria and 5) that generates knowledge that will inform improvements in child welfare practice and policy. Methods The first three research questions will be addressed through a longitudinal quantitative study involving children and adolescents (aged 11–21 years), their parents, and professionals working in residential care settings. Standardized surveys will be administered at multiple time points to track developmental changes and identify influencing factors. In addition, to gain a deeper understanding of the implicit mechanisms, and everyday practices of residential care, we plan to implement accompanying qualitative methods adapted to the particular circumstances of the field of research. Finally, a communicative validation process will be used to discuss and reflect on preliminary findings with professionals in the field. This step ensures the relevance of the results and supports the development of practice-oriented knowledge for quality improvement and safeguarding in child welfare services. Discussion This first-of-its-kind study in Austria combines quantitative and qualitative methods to generate evidence for child welfare practice and policy. An innovative element is the potential development of a standardized documentation tool to support research and quality assurance. Challenges include the field’s complexity, participant recruitment, and risk of participation fatigue, which require close collaboration with practitioners and flexible survey strategies to ensure relevant results.